The Ibāḍī Traders of Bilād al-Sūdān - van Riel, Jason (AUC Knowledge Fountain, 2012)
This thesis deals with the trans-Saharan commercial links between the Maghreb and Bilād al-Sūdān from the 1st till 5th century AH, and the role the Ibāḍī Traders « community played in establishing these links. Ibāḍī Traders of Bilād al-Sūdān« merchants monopolized the trans-Saharan trade due to their alliances with local Berber tribes and their predisposition to trade, dating from their inception history in Basra. Missionary efforts by Ibāḍī Traders « traders to Bilād al-Sūdān led to the introduction of Islam in Bilād al-Sūdān, as well as the introduction of other Islamic traditions and customs. Both religion and trade where of the utmost importance for the Barbers « community in the Maghreb and thus a compromise between both had to be found. With the research presented in this thesis, I will show how the Ibadi Traders « community became the most important player in trans-Saharan trade and how they were able to hold on to this position until their demise at the beginning of the 4th century. Another significant result of trans-Saharan trade is the considerable impact that Ibadi traders had on both religious and cultural customs of the people of Bilād al-Sūdān. As a side note I will also tentatively argue that the importance of trade for the Ibāḍī community in the Maghreb must have had some influence on the way Ibadism manifested itself.